MENGGALI KEARIFAN LOKAL MELALUI KAJIAN ETNOARKEOLOGI - Gunadi Kasnowihardjo (BRIN, 2009)
Local wisdom inherited by our ancestors has gradually been abandoned by present generation. Local wisdom actually taught us to live harmoniously with the surrounding environtment. As such, the environtment should be well - preserved for human own purposes. Ethno-archaeological studies could be used to unearth local wisdom of certain community or ethnic group. Eventually, this will provide added value to archaeological research.